Implementasi Kecerdasan Buatan dan Chatbot dalam Konseling Pastoral: Potensi dan Tantangan - Kinoto Christian; Daryanto Daryanto (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This study explores the opportunities and threats of implementing artificial intelligence (AI) and chatbots in pastoral church/Christian community counseling. With the rapid progression of technology, AI has the potential to influence various aspects of life, including pastoral counseling. The key opportunities highlighted include improved accessibility of pastoral counseling, consistent support, and advancement in data analysis. However, there are also threats related to AI and chatbot implementation, such as the lack of 'human touch' in counseling, data privacy challenges, and potential misinterpretation by AI. This study provides an overall perspective of AI and chatbots, references several case studies where this technology has been implemented in similar contexts and focuses on potential risks and benefits. The research aims to understand how the future of pastoral counseling could be influenced by AI and chatbot implementation and stimulate dialogue on how the church could respond to this technological development.